2015
DOI: 10.1063/1.4921199
|View full text |Cite
|
Sign up to set email alerts
|

The detection and subsequent volume optimization of biological nanocrystals

Abstract: Identifying and then optimizing initial crystallization conditions is a prerequisite for macromolecular structure determination by crystallography. Improved technologies enable data collection on crystals that are difficult if not impossible to detect using visible imaging. The application of second-order nonlinear imaging of chiral crystals and ultraviolet two-photon excited fluorescence detection is shown to be applicable in a high-throughput manner to rapidly verify the presence of nanocrystals in crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Several papers have described techniques to identify micro-crystallization conditions using vapour diffusion. Luft et al (2015) and Lee et al (2018) both showed how nonlinear optics could be used to identify conditions which favour micro-(and nano-)crystalline growth in 96-well sittingdrop plates. Lee et al (2018) also showed how adapting the vapour diffusion protocol using a 'controlled evaporation' approach increases the propensity for micro-crystallization.…”
Section: The Re-emergence Of Batch Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have described techniques to identify micro-crystallization conditions using vapour diffusion. Luft et al (2015) and Lee et al (2018) both showed how nonlinear optics could be used to identify conditions which favour micro-(and nano-)crystalline growth in 96-well sittingdrop plates. Lee et al (2018) also showed how adapting the vapour diffusion protocol using a 'controlled evaporation' approach increases the propensity for micro-crystallization.…”
Section: The Re-emergence Of Batch Methodsmentioning
confidence: 99%
“…This paper will focus on the process of transitioning from a small-scale (<0.2-2.0 ml) vapour diffusion experiment to a large-scale (!100 ml) batch protocol. Techniques such as second-order nonlinear imaging of chiral crystals (SONICC) (Luft et al, 2015;Lee et al, 2018) and dynamic light scattering (Abdallah et al, 2015), although extremely useful in identifying conditions with micro-crystals, are not yet in the standard crystallographers' toolbox and have, therefore, been avoided here. The tools that are described herein were chosen for either their widespread adoption or their relatively low cost, in the hope that the methods proposed are translatable to the majority of crystallization laboratories.…”
Section: Transitioning From Vapour Diffusion To Batchmentioning
confidence: 99%
“…We have worked with crystallization metadata from the HTX Center historical database, as well as data mined from the PDB, to try to detect patterns and to advance our understanding of the chemical crystallization space that yields protein crystals (Lynch et al, 2020;Fusco et al, 2014;Altan et al, 2016). These internal metadata coupled with knowledge of the outcome have also been used to identify ligands that have previously been missed (Bruno et al, 2014) and to adapt processes to the capabilities of new sources such as X-ray free-electron lasers (Luft et al, 2015). The HTX Center also develops computational approaches that can be used by others, as shown by the MARCO algorithm for classifying crystallization outcomes (Bruno et al, 2018) and its implementation into the MARCO Polo GUI (Holleman et al, 2021).…”
Section: Looking Forwardmentioning
confidence: 99%
“…Before the sample is added, the oil-filled plates are loaded with cocktail, centrifuged and imaged by a video microscope system (as a control), then loaded with sample, centrifuged again and imaged again, first immediately after the sample has been added and then weekly, usually for a period of six weeks. At the week-four point, second-order nonlinear imaging of chiral crystals (SONICC) and two-photon emitted fluorescence (TPEF) imaging also take place (Luft et al, 2015). The individual images are stored and made available in a compressed .rar format file.…”
Section: Applicationmentioning
confidence: 99%